Philosophische Theologie im Umbruch (II/2) Wider den ungöttlichen Gott (II/2): Moderner Atheismus im Raum der Metaphysik - Wucherer-Huldenfeld, Augustinus Karl (2015)
Part of Philosophical Theology in Transition (Vol. II/2): Atheistic Philosophers after Hegel and den scotistisch Tradition, wich obscures an phaenomenological and existential understanding of being (creation) as a gift, reject the existence of God to protect human dignity, independence and liberty, developed their own ontologies and are not postmetaphysical thinkers.